2009
DOI: 10.1038/mt.2008.232
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances the Replication of Oncolytic Herpes Simplex Virus

Abstract: Hypoxia contributes to the resistance of tumors to conventional therapies. We hypothesized that their replication in hypoxic environments like brain or oral mucosa would make oncolytic herpes simplex viruses (HSVs) such as G207 (which has undergone clinical trials) replicate to a greater extent in hypoxic tumors like glioblastoma. Hypoxic cultured U87 cells yielded 4% more wild-type HSV (P = 0.04) and 3.6-fold more G207 (P = 0.001) after 48 hours of infection when compared with normoxic cells. Real-time RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 36 publications
2
60
1
Order By: Relevance
“…Concerning hepatocytes, low oxygen is essential for the preservation of their structure and metabolism (19). Moreover, hypoxia affects the replication of several viruses (20)(21)(22)(23)(24)(25)(26).Based on these observations, we studied the impact of oxygen tension on HCV replication and virus production in human hepatoma (Huh7) cells. We show that low oxygen selectively enhances HCV RNA replication at an early stage and in a hypoxia-inducible factor (HIF)-independent manner.…”
mentioning
confidence: 99%
“…Concerning hepatocytes, low oxygen is essential for the preservation of their structure and metabolism (19). Moreover, hypoxia affects the replication of several viruses (20)(21)(22)(23)(24)(25)(26).Based on these observations, we studied the impact of oxygen tension on HCV replication and virus production in human hepatoma (Huh7) cells. We show that low oxygen selectively enhances HCV RNA replication at an early stage and in a hypoxia-inducible factor (HIF)-independent manner.…”
mentioning
confidence: 99%
“…One hallmark of GBM is the presence of a hypoxic microenvironment, which has been shown to maintain GSC stemness. 54 In contrast to other therapies, G207 replicated better in glioma cell lines in vitro under hypoxic compared with normoxic conditions, 55 while G47Δ replicated similarly in hypoxic and nonhypoxic regions of GSC-derived tumors. 56 …”
Section: Cytotoxic Gene Therapy Oncolytic Viruses Herpes Simplex Virusmentioning
confidence: 98%
“…It has been reported that oncolytic HSV-1 replicates preferentially in the hypoxic environment. 20) We constructed a fusion protein between amino terminal region of ICP4, a transcription factor essential for viral replication, and a 56 amino-acid sequence regulating oxygen-dependent protein degradation of HIF1a. In this oncolytic HSV-1, ICP4 protein is degraded in the normoxic condition and is expressed in the hypoxic condition.…”
Section: Fig 3b Expression Of Calponin 1 In Mesothelioma Cellsmentioning
confidence: 99%